Bioenergeticheskoe modelirovanie sorevnovatel'noi deyatel'nosti sil'neishchikh lyzhnikov-gonshchikov na XVII zimnikh Olimpiiskikh igrakh (Nagano, 1998) - Ramenskaya, T. I. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
High variety of an organism functioning - is the specific of competitive activity of ski-racers on the billowy ground tracks.The new classification of ski-racing tracks was suggested by the author. Metric and temporal parameters of one's competitive activity on the ascensions, on the flat sectors and on the descents were defined by the analysis of profiles of Nagano '98 tracks. Prevailing metabolic ways for energy supplying of one's competitive activity on short(less than 15 km) and on long (more than 30 km) distances were defined. An efficiency of the "profiled" preparing for most powerful ski-racers to XIX (Salt-Lake City, 2002)and following Winter Olympics, was substantiated. Principals of the "profiled" preparing are built up on the base of inquired consistent patterns of motor and energetical characteristics of Nagano'98 ski-racers' performance.